DAKWAH RETORIS DALAM KARYA SASTRA NOVEL “HABIBIE & AINUN” KARYA BJ. HABIBIE - Rahmah, Mariyatul Norhidayati (Jurnal Ilmu Dakwah, 2014)
There should be at least four rethorical principles in conducting da’wah. The first principle is an emotional appeal, which means a kind of touching da’wah communication that involves emotions, expectation and affection of the mad’u. Secondly, the da’i (preacher) should use persuasive and gently ways as well as clear and understandable languages. Thirdly, he should understand the condition of community so his da’wah could become soothing. The last principle is enabling to give strong arguments. The novel might become a medium to deliver the messages of da’wah. The novel of Habibie & Ainun does not only a philological and romance novel, but also a kind of cultural, political and da’wah novel. Its feature is not only in using rhetorical language, but indeed it was also written based on personal stories including his life experiences and love story of a religious man that tremendously inspires the readers. In this novel, the rhetorical da'wah is expressed in various ways following the context of life journey as well as the writer’s mood and passion namely kinds of persuasive and touching da’wah, contextual da’wah, and argumentative rethorical da’wah.***Prinsip Retorika dalam berdakwah paling tidak mengandung empat hal:  emotional appeals (imbauan emosional) yakni sebuah tindak komunikasi dakwah yang menyentuh hati sasaran dakwah, melibatkan emosi, harapan dan kasih sayang;menggunakan bahasapersuasive, lemah lembut, jelas, dan mudah dipahami; memahami kondisi masyarakat sehingga mengarah pada dakwah yang menyejukkan hati; dan disertai dengan argumentasi yang kuat. Novel dapat digunakan sebagai media untuk menyampaikan pesan-pesan dakwah.Novel Habibie & Ainun, bukan hanya novel sastra dan novel cinta, tetapi juga novel budaya, politik dan novel dakwah.Dan keistimewaan Novel Habibie & Ainun ini disamping bahasanya yang retoris, adalah lebih dari sekedar sebuah cerita, novel ini ditulis oleh pengarangnya berdasarkan kisah pribadi, apa yang terjadi dalam hidupnya, sebuah kisah cinta insan beriman yang memberi insprirasi yang luar biasa bagi pembaca. Dakwah retoris dalamnovel ini terpancar dalam berbagai bentuk mengiringi situasi perjalanan hidup, kejiwaan dan emosi sang penulis, ada dakwah retoris menyentuh hati, persuasive, memperhatikan kondisi sasaran dakwah hingga retorika argumentatif.